LITERATURE REVIEW: ANALYSIS OF INDONESIA'S READINESS TO FACE THE ACCELERATION OF DIGITAL ECONOMIC TRANSFORMATION: KAJIAN LITERATUR: ANALISIS KESIAPAN INDONESIA MENGHADAPI AKSELERASI TRANSFORMASI EKONOMI DIGITAL - Isnawati, Dian; Rosita Pangestika, Ratna; Lestari, Wahyu; Intan Prabandari, Anandhiya (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
The policies prepared by the government to accelerate digital transformation in Indonesia can be considered ready, both in terms of infrastructure, human resources (HR), and government regulations. This is evident from the projects that have been implemented by the government. From the explanations previously presented, it is stated that the number of internet users in Indonesia has been increasing year by year. This is also influenced by the fact that during the COVID-19 pandemic, digital technology users were facilitated in carrying out their activities. This digital transformation requires the community to adapt to new habits, encouraging them to innovate and find ways to sustain their livelihoods by utilizing digital technology. As a result, people will become accustomed to these changes, transitioning into a digital economy society. Indonesia's readiness to accelerate digital transformation is almost fully prepared, though there are minor obstacles in the field that are sometimes beyond the government's control.